Belgium : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Insurance Supervision and Regulation, and Securities Settlement Systems. (IMF Staff Country Reports; Country Report, 2006)
This paper discusses key findings of the Financial System Stability Assessment (FSSA) and Reports on the Observance of Standards and Codes (ROSC) on Banking Supervision, Securities Regulation, Insurance Supervision and Regulation, and Securities Settlement Systems for Belgium. The assessment reveals that overall, the financial system is generally sound, resilient to potential adverse shocks, and well supervised. Risks both on the international level and domestically appear well within the banks' capacity to manage them and are well understood by the supervisor and overseer of the system.